A Rare Case of Histiocytic Sarcoma Secondary to Gastrointestinal Stromal Tumor in the Stomach: Transdifferentiation or Synchronicity? - Jiankun Tong; Jean Luo; Pierre F. Saldinger; William H. Rodgers (Case Reports in Hematology)
Histiocytic sarcoma is a rare malignant histiocytic neoplasm composed of cells with morphologic and immunophenotypic features of mature tissue histiocytes. It occurs anywhere in the body and behaves aggressively. However, its etiology is unknown. Here, we report a 68-year-old female who developed histiocytic sarcoma following chemotherapy with imatinib (Gleevec) for gastrointestinal stromal tumor. Possible mechanisms of transdifferentiation from gastrointestinal stromal tumor to histiocytic sarcoma are discussed based on the features of our case and other two similar cases in the literature.